2019
DOI: 10.3389/fimmu.2018.03174
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Wheat Amylase Trypsin Inhibitors Increases Their Innate and Adaptive Immunostimulatory Potential in vitro

Abstract: Amylase trypsin inhibitors (ATI) can be found in all gluten containing cereals and are, therefore, ingredient of basic foods like bread or pasta. In the gut ATI can mediate innate immunity via activation of the Toll-like receptor 4 (TLR4) on immune cells residing in the lamina propria, promoting intestinal, as well as extra-intestinal, inflammation. Inflammatory conditions can induce formation of peroxynitrite (ONOO−) and, thereby, endogenous protein nitration in the body. Moreover, air pollutants like ozone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…On the other hand, ATIs could be an “interesting” pathogenetic candidate. Although different polymorphisms of Toll-like receptor 4 (TLR4) have not been found in celiac disease [ 119 ], it seems that the TLR4-MD2-CD14 complex may be a potent activator of innate immune responses in monocytes, macrophages, and dendritic cells through Toll-like receptors and may play a role in NCWS [ 60 , 120 , 121 ]. MD2 is a secreted protein that interacts with TLR4, binds the lipid A moiety of lipopolysaccharides, and facilitates the creation of TLR4 dimers that are intimately required for downstream signaling and activation of the NF-κB (nuclear factor kappa light chain enhancer of activated B cells) pathway, while CD14 is a glycosyl-phosphatidylinositol (GPI)-linked protein found on the cell membrane in lipid rafts (microdomains at the plasmatic membrane with definite lipid and protein composition) and functions to transfer lipopolysaccharides from the bacterial cell wall to the MD2/TLR4 complex [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ATIs could be an “interesting” pathogenetic candidate. Although different polymorphisms of Toll-like receptor 4 (TLR4) have not been found in celiac disease [ 119 ], it seems that the TLR4-MD2-CD14 complex may be a potent activator of innate immune responses in monocytes, macrophages, and dendritic cells through Toll-like receptors and may play a role in NCWS [ 60 , 120 , 121 ]. MD2 is a secreted protein that interacts with TLR4, binds the lipid A moiety of lipopolysaccharides, and facilitates the creation of TLR4 dimers that are intimately required for downstream signaling and activation of the NF-κB (nuclear factor kappa light chain enhancer of activated B cells) pathway, while CD14 is a glycosyl-phosphatidylinositol (GPI)-linked protein found on the cell membrane in lipid rafts (microdomains at the plasmatic membrane with definite lipid and protein composition) and functions to transfer lipopolysaccharides from the bacterial cell wall to the MD2/TLR4 complex [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…We focused on ATI and nitrated ATI, which have been identified as stimulating the TLR4/NF-κB pathway in macrophages and dendritic cells. 33,39 Using different quantitative analysis methods, we found that the majority of TLR4 molecules are already located in clusters, whereby pronounced differences existed among the donors already in the unstimulated state. Upon stimulation with LPS or ATI, the overall fraction of clustered TLR4 molecules increased.…”
Section: Discussionmentioning
confidence: 98%
“…Our prior studies have shown that TLR4 can be stimulated by amylase trypsin inhibitors (ATI) from wheat and thus act as natural activators of innate immunity in monocytes, macrophages and dendritic cells. 7,[33][34][35][36][37][38][39] Moreover, ATI are major allergens in Baker's asthma. 40 ATI are a family of non-gluten proteins found in different cereals containing gluten such as wheat, rye or barley.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATIs represent 2%-4% of total wheat protein and are believed to induce an innate immune response via activation of the Toll-like receptor 4 (TLR4) on immune cells within the intestine. They have also been shown to be involved in an adaptive immune response, have been implicated in coeliac disease, and may also contribute to inflammation in other disorders [48][49][50][51]. Additionally, legumes, which have a higher protein content than cereals, contain significant levels of anti-nutritional factors such as lectins and trypsin inhibitors, and two major storage proteins, vicilins and legumins, which are all resistant to proteolysis in the small intestine [46,52,53].…”
Section: Resistant Proteins-beyond Glutenmentioning
confidence: 99%